2023
DOI: 10.3390/brainsci13020237
|View full text |Cite
|
Sign up to set email alerts
|

Blood Levels of Neuropeptide 26RFa in Relation to Anxiety and Aggressive Behavior in Humans—An Exploratory Study

Abstract: 26RFa, also referred to as QRFP, is a hypothalamic neuropeptide mainly known for its role in the regulation of appetite and glucose metabolism. Its possible relevance to emotional regulation is largely unexplored. To address this, in the present exploratory study, we analyzed the plasma concentrations of 26RFa in humans characterized by different levels of anxiety and aggressive behavior. For this purpose, the study included 13 prison inmates who have committed violent crimes and 19 age-matched healthy men fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…In agreement with these data, another study established anxiolytic effect of GPR103 (QRFP) receptor agonist in mice [41]. Interestingly, a recent human study on aggressive individuals revealed that the plasma levels of QRFP positively correlated with the anxiety scores in all the studied subjects and controls [42]. Nevertheless, in our study QRFP applied into the LHA did not modify general locomotion, nor the anxiety level of tested animals (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with these data, another study established anxiolytic effect of GPR103 (QRFP) receptor agonist in mice [41]. Interestingly, a recent human study on aggressive individuals revealed that the plasma levels of QRFP positively correlated with the anxiety scores in all the studied subjects and controls [42]. Nevertheless, in our study QRFP applied into the LHA did not modify general locomotion, nor the anxiety level of tested animals (Figs.…”
Section: Discussionsupporting
confidence: 91%